Corruption in Europe: Recent Developments - Ada-Iuliana Popescu (CES Working Papers, 2014)
Reducing corruption is one of the world's many challenges. The fight against corruption is often discouraging. Yet, Europe continues to advance its anti-corruption initiatives. While the fight against has seen some victories, significant gains are few, especially in the Central and South European countries, where corruption is deeply rooted in the ordinary life of their citizens. Indeed, the latest reports from private organizations and public bodies show that no European country is sheltered from corruption. This article discusses some of the latest European developments in the fight against corruption.
Keywords: D73; H83; K42; 330; corruption; corrupt practices; anti-corruption initiatives; corporate corruption Romania